Stiffness of HIV‐1 Mimicking Polymer Nanoparticles Modulates Ganglioside‐Mediated Cellular Uptake and Trafficking - Behnaz Eshaghi; Nourin Alsharif; Xingda An; Hisashi Akiyama; Keith A. Brown; Suryaram Gummuluru; Björn M. Reinhard (Advanced Science, 2020)
Abstract The monosialodihexosylganglioside, GM3, and its binding to CD169 (Siglec‐1) have been indicated as key factors in the glycoprotein‐independent sequestration of the human immunodeficiency virus‐1 (HIV‐1) in virus‐containing compartments (VCCs) in myeloid cells. Here, lipid‐wrapped polymer nanoparticles (NPs) are applied as a virus‐mimicking model to characterize the effect of core stiffness on NP uptake and intracellular fate triggered by GM3‐CD169 binding in macrophages. GM3‐functionalized lipid‐wrapped NPs are assembled with poly(lactic‐co‐glycolic) acid (PLGA) as well as with low and high molecular weight polylactic acid (PLAlMW and PLAhMW) cores. The NPs have an average diameter of 146 ± 17 nm and comparable surface properties defined by the self‐assembled lipid layer. Due to differences in the glass transition temperature, the Young's modulus (E) differs substantially under physiological conditions between PLGA (EPLGA = 60 ± 32 MPa), PLAlMW (EPLAlMW = 86 ± 25 MPa), and PLAhMW (EPLAhMW = 1.41 ± 0.67 GPa) NPs. Only the stiff GM3‐presenting PLAhMW NPs but not the softer PLGA or PLAlMW NPs avoid a lysosomal pathway and localize in tetraspanin (CD9)‐positive compartments that resemble VCCs. These observations suggest that GM3‐CD169‐induced sequestration of NPs in nonlysosomal compartments is not entirely determined by ligand–receptor interactions but also depends on core stiffness.